2021
DOI: 10.1007/s11154-021-09655-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypocalcemia in COVID-19: Prevalence, clinical significance and therapeutic implications

Abstract: COVID-19 extra-pulmonary features include several endocrine manifestations and these are becoming strongly clinically relevant in patients affected influencing disease severity and outcomes. At the beginning of COVID-19 pandemic no population data on calcium levels in patients affected were available and in April 2020 a first case of severe acute hypocalcemia in an Italian patient with SARS-CoV-2 infection was reported. Subsequently, several studies reported hypocalcemia as a highly prevalent bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 100 publications
5
67
1
Order By: Relevance
“…Some papers have now highlighted an emerging osteo-metabolic phenotype of COVID-19, which might influence COVID-19 severity and clinical outcomes. This phenotype is typically characterized by widespread acute hypocalcaemia and chronic hypovitaminosis D, as well as a high prevalence of morphometric vertebral fractures 2 4 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Some papers have now highlighted an emerging osteo-metabolic phenotype of COVID-19, which might influence COVID-19 severity and clinical outcomes. This phenotype is typically characterized by widespread acute hypocalcaemia and chronic hypovitaminosis D, as well as a high prevalence of morphometric vertebral fractures 2 4 .…”
mentioning
confidence: 99%
“…This report suggested that COVID-19 was a possible precipitating cause of subclinical post-surgical hypoparathyroidism 5 . Interestingly, previous reports on patients with SARS and Ebola virus infection had described hypocalcaemia as a highly prevalent biochemical abnormality, ranging from 60% of patients at hospital admission to 75% during hospitalization 2 .…”
mentioning
confidence: 99%
See 3 more Smart Citations